Effects of selenium in comparison to exendin-4 on the expression of GLP-1R, IRS-1 and preproinsulin in the pancreas of diabetic rats - Rizk, Sandra (2016)
Antioxidant supplements are considered as being favorable for the treatment of diabetes mellitus. There is a debate regarding the effect of selenium on the incidence of diabetes mellitus: even though some clinical trials studies suggested that high selenium supplementation resulted in an increased risk of incidence of diabetes mellitus, other studies showed that the level of serum selenium in diabetic patients was lower than its level in nondiabetic subjects, and high selenium status may exert a protective action against the incidence of diabetes mellitus. Exendin-4 is a GLP-1 agonist with antidiabetic properties. It binds and activates GLP-1R with greater potency than GLP-1 and is used in the treatment of diabetes mellitus. The mechanisms by which selenium and exendin-4 exert their antidiabetic actions are still unclear. In this study, we investigated the effects of selenium or exendin-4 administration on the expression of glucagon-like peptide-1 receptor (GLP-1R), insulin receptor substrate-1 (IRS-1), and preproinsulin in the pancreas of diabetic rats. Diabetes was induced by streptozotocin administration. Diabetic rats were injected intraperitonially with 0.03 μg exendin-4/kg body weight/daily or treated with 5 ppm selenium in drinking water for a period of 4 weeks. Results obtained indicate that GLP-1R and IRS-1 levels decreased while the level of preproinsulin mRNA increased in the pancreas of diabetic untreated rats, as compared to control rats. Treatment of diabetic rats with exendin-4 increased protein and mRNA levels of GLP-1R, and IRS-1, as well as the mRNA level of preproinsulin in the pancreas, as compared to their levels in diabetic untreated rats. Selenium treatment of diabetic rats increased the pancreatic mRNA levels of GLP-1R, IRS-1, and preproinsulin. The numbers of pancreatic islets and GLP-1R molecules in the pancreas of diabetic rats was also increased upon treatment with selenium or Exendin-4. Therefore, exendin-4 and selenium may exert their antidiabetic effects by increasing GLP-1R, IRS-1, and preproinsulin expression in the pancreas and by increasing the number of pancreatic islets.